Kepuasan Tamu Di Hotel Kamaniiya Petitenget Seminyak Yang Dipengaruhi Oleh Kualitas Pelayanan Dan Fasilitas - Healthy, Gede Dodi; Wirya, I Made Suwitra; Susila, I Made Gede Darma (Universitas Triatma Mulya, 2023)
This study aims to determine the influence of service quality and facilities on guest satisfaction. The location of this research is in Kamaniiya Petitenget Seminyak. The data collection techniques used are observation and questionnaires. The population used Kamaniiya Petitenget Seminyak guests, with a sample of 150 respondents. The data analysis techniques used were Descriptive Statistical Analysis, Data Instrument Test, Classical Assumption, Multiple Linear Regression, t, and Determination. Based on the results of the study, it was obtained that the quality of service has a positive and significant influence on guest satisfaction, facilities have a positive and significant influence on guest satisfaction, service quality and facilities have an influence of 60% on guest satisfaction. The suggestion that can be given by the researcher is to routinely provide training to employees, so that later employees will be able to communicate well when providing services to guests, increase wifi speed and always provide quick responses to guests, provide detailed information, pay attention to guests.